In a while or two we will find the tone essays and proposals, curatorial concepts, and critiques - Ndikung, Bonaventure Soh Bejeng 1977- (ARCHIVE Books, 2020)
This collection of writings from Bonaventure Soh Bejeng Ndikung presents, for the first time in one volume, essays and proposals edited anew. Ndikung?s expanded curatorial practice delineates the space of exhibition making as a space of critical thinking and of experimentation. By proximity, these texts echo each other, resonate with each other, interfere with each other, and present perspectives on the political, poetic, and philosophical potentials of exhibition making, beyond the tight corset of the discipline itself.
Keywords: Kunstausstellung; Kurator -- Museumskunde